Temporal dynamics of CD8+ T cell effector responses during primary HIV infection. - Demers, KR; Makedonas, G; Buggert, M; Eller, MA; Ratcliffe, SJ; Goonetilleke, N; Li, CK; Eller, LA; Rono, K; Maganga, L; Nitayaphan, S; Kibuuka, H; et al. (Public Library of Science, 2016)
The loss of HIV-specific CD8+ T cell cytolytic function is a primary factor underlying progressive HIV infection, but whether HIV-specific CD8+ T cells initially possess cytolytic effector capacity, and when and why this may be lost during infection, is unclear. Here, we assessed CD8+ T cell functional evolution from primary to chronic HIV infection. We observed a profound expansion of perforin+ CD8+ T cells immediately following HIV infection that quickly waned after acute viremia resolution. Selective expression of the effector-associated transcription factors T-bet and eomesodermin in cytokine-producing HIV-specific CD8+ T cells differentiated HIV-specific from bulk memory CD8+ T cell effector expansion. As infection progressed expression of perforin was maintained in HIV-specific CD8+ T cells with high levels of T-bet, but not necessarily in the population of T-betLo HIV-specific CD8+ T cells that expand as infection progresses. Together, these data demonstrate that while HIV-specific CD8+ T cells in acute HIV infection initially possess cytolytic potential, progressive transcriptional dysregulation leads to the reduced CD8+ T cell perforin expression characteristic of chronic HIV infection.